Concordance in the healthcare context: A concept analysis - Taiwong, Anucha; Uppor, Wassana; Vibulchai, Nisakorn (Belitung Nursing Journal, 2024)
Background: The concept of concordance and its usage are indicative of patient-centered healthcare, which encourages an equitable collaboration between patients and clinicians. However, there is a lack of clarity in understanding concordance, and an analysis of this concept is warranted. Objective: This paper seeks to explore the essence of the concordance concept in the healthcare context. Methods: Walker and Avant’s eight-step method of concept analysis was applied. A literature search was conducted using concordance AND concord as keywords on CINAHL, MEDLINE, PubMed, ProQuest, Cochrane database, and ScienceDirect databases, published between 2006 and 2022. Results: The attributes of concordance include communication process, therapeutic partnership, and agreement on treatment regimens. Antecedents of concordance comprise provider-patient relationship, patients’ beliefs, healthcare providers’ characteristics, and complexity of treatment plans. Consequences are improved adherence and compliance, improved clinical outcomes, and better quality of life. Conclusion: This paper offers clarification of concordance by presenting its antecedents, attributes, and consequences. The findings serve as a basis for developing assessments and nursing interventions to promote patient concordance. Nurses can use the findings to encourage concordance by establishing a trusty relationship during health encounters that respects patients’ beliefs and effectively communicating to improve patients’ understanding in dealing with complex treatment plans.